Hepatic adverse events during highly active antiretroviral therapy containing nevirapine: a case report - Yamazhan Tansu; Gökengin Deniz (BMC, 2002)
Abstract Background Hepatotoxicity is one of the most serious complications of highly active antiretroviral therapy (HAART). The aim of this report is to analyse an HIV infected patient on HAART including nevirapine and taking antidepressive agents, with acute toxic hepatitis. Case presentation A 39 year old patient diagnosed as HIV positive one month ago administered to the clinical ward of the Department of Infectious Diseases and Clinical Microbiology in Ege University Medical School with high fever, malaise, nausea, diarrheae and elevated liver enzymes (ALT 1558 U/L, AST 4288 U/L). He has been using HAART including zidovudine+lamivudine (2 × 1/day) and nevirapine (2 × 200 mg/day, following dose escalation) for 22 days, sertralin and diazepam for 12 days and lithium for 10 days. The patient was hospitalized. Antiretroviral and antidepressant treatments were stopped. The day after admission, his fever dropped and his symptoms improved. Clinical improvement continued on the following days. The patient was discharged upon his request on the 14th day of hospitalization. The liver function tests returned to normal levels in two weeks following discharge. Conclusion Close monitoring of liver enzymes during the first 12 weeks of nevirapine therapy is critical to prevent life threatening events.